Indonesian Media Framing Analysis of Recep Tayyip Erdoğan in the 2023 Turkish Presidential Election - Yenis Contesa; Riswanda Imawan; Sigit Hardiyanto; Adang Aldhila; Faizal Hamzah Lubis; Agung Saputra; Fanny Anggun Abadi (AlAdzkiya International of Education and Sosial (AIoES) Journal, 2026)
Presidential elections in Turkey always attract global attention, as Turkey is a country that has significant influence in the international arena. This article aims to analyse national media framing sentiment in Indonesia towards Erdoğan in the 2023 Turkish presidential election. This article uses framing theory to analyse media coverage of the Turkish presidential election and the post-election period from March to August 2023. The author reads news from three Indonesian media outlets namely CNN Indonesia, BBC Indonesia, and CNBC Indonesia to see how they framed the news about Erdoğan. The purpose of this framing analysis was to determine whether the coverage of Erdoğan was positive, negative or neutral. The results of this study show that the highest percentage of national media framing in Indonesia is neutral. Erdoğan was often reported with negative sentiments, especially in relation to his controversial policy issues. News with positive sentiments towards Erdoğan was the lowest. In fact, after the election, news coverage tended to be neutral. This shows that national media in Indonesia generally endeavour to maintain objectivity and professionalism in news coverage, by balancing various perspectives and not leaning too much towards certain sentiments. This research fills a gap in international media studies by focusing on how Indonesian national media framed news coverage of Erdoğan during the 2023 Turkish presidential election. While many studies examine media framing in Western countries, this research provides new insights into media perspectives from developing countries such as Indonesia, which is important for understanding regional views on global leaders.